Validation of Biomarkers and Immunotherapy With Crohn’s Disease Using WGCNA and Two-Sample Mendelian Randomization Study - Cong Hu; Shuxiong Nong; Chenang Liu; Yongfeng Chen; Chilin Liao; Meng Wu (Gastroenterology Research and Practice, 2025)
Conclusions: The study screened five potential biomarker genes in CD patients using a bioinformatics approach and Mendelian randomization study. Our results provided insights into CXCL1, LCN2, NOS2, S100A8, and DUOX2 in CD and suggested that CXCL1 may potentially be the optimal biomarker that could be a relatively easy path to clinical translation.